Crossing the Caste and Ethnic Boundaries: Love and Intermarriage Between Madhesi Men and Pahadi Women in Southern Nepal - Chudamani Basnet; Ratnakar Jha (South Asia Multidisciplinary Academic Journal)
In South Asia, marriages are overwhelmingly endogamous. In recent years, new forms of self-initiated marriages, such as love-marriages and love-arranged marriages, are beginning to emerge among the younger generation. In these new forms, young people exercise considerable choice and agency; however, when the couple crosses caste and ethnic boundaries, parents and kin often take the defiance of the younger generation as instances of dereliction of duty and transgression of family and community values. Cases of intermarriage, thus, offer a unique opportunity to investigate the social and cultural changes a society is undergoing. Based on qualitative research, conducted in southern Nepal, this paper examines the ways Madhesi (plains dwellers) men and Pahadi (hill dwellers) women enter into courtship and negotiate their marriages. We argue that new forms of subjectivity emphasizing individual choice and agency have begun to emerge among the younger generation in Nepal—and South Asia in general. The new subjectivity has unfolded in tandem with structural transformations of the economy, the state, and the culture.